The utility of FDG-PET in the diagnosis of thymic epithelial tumors - Otsuka, Hideki (The Journal of Medical Investigation, 2012)
In this article, seven studies evaluating the utility of FDG-PET in the diagnosis of thymic epithelial tumors were reviewed and the results of an investigation conducted in Tokushima University Hospital are reported. FDG accumulation of low-risk thymoma is low, and FDG accumulation of thymic carcinoma is high. High-risk thymoma exhibits various degrees of accumulation and a definite conclusion has not yet been reached; however, overall, the higher the histological grade, the higher the FDG accumulation becomes, suggesting that this is correlated to staging. Our data also support the previous reports. FDG-PET may indicate lymph node metastasis and distant metastasis, which are sometimes difficult to detect using other modalities. When lymph node metastasis and/or distant metastasis are suspected in addition to thymic lesions, FDG-PET/CT, which allows for searching of the entire body at once, is useful. FDG-PET/CT is effective for estimating histopathological malignancy and staging in the diagnosis of thymic epithelial tumors and can be an important imaging test with high relevance to the prognosis of a patient. J. Med. Invest. 59: 225-234, August, 2012